2021
DOI: 10.3390/ijerph19010351
|View full text |Cite
|
Sign up to set email alerts
|

Lockdown-Associated Hunger May Be Affecting Breastfeeding: Findings from a Large SMS Survey in South Africa

Abstract: The impact that the COVID-19 pandemic has had, and will continue to have, on food security and child health is especially concerning. A rapid, Short Message Service (SMS) Maternal and Child Health survey was conducted in South Africa in June 2020 (n = 3140), with a follow-up in July 2020 (n = 2287). This was a national cross-sectional survey conducted among pregnant women and mothers registered with the MomConnect mhealth platform. Logistic regression was conducted to explore the associations between breastfee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The major reason women gave for not practicing EBF (mixed feeding prevalence 61%) in the current study was that they perceived that they did not have enough milk. Similar findings were reported in a survey conducted in the Eastern Cape, South Africa ( 21 ). The survey found that early introduction of food, water, and infant formula milk was common despite a high breastfeeding initiation rate ( 21 ).…”
Section: Discussionsupporting
confidence: 91%
“…The major reason women gave for not practicing EBF (mixed feeding prevalence 61%) in the current study was that they perceived that they did not have enough milk. Similar findings were reported in a survey conducted in the Eastern Cape, South Africa ( 21 ). The survey found that early introduction of food, water, and infant formula milk was common despite a high breastfeeding initiation rate ( 21 ).…”
Section: Discussionsupporting
confidence: 91%
“…Preference for home deliveries increased Balogun et al [ 30 ] Challenges in access and satisfaction with reproductive, maternal, newborn and child health services in Nigeria during the COVID-19 pandemic: A cross-sectional survey PLoS ONE Cross sectional study Nigeria Client satisfaction with reproductive, maternal, newborn and child health services The COVID-19 lockdown posed challenges to accessing RMNCH services for many of the women who were surveyed. Overall satisfaction with care was high Sayed et al [ 31 ] Lockdown-associated hunger may be affecting breastfeeding: findings from a large SMS survey in South Africa International journal of environmental research & public health Cross-sectional study South Africa Breastfeeding, maternal depression and hunger Breastfeeding initiation rates was high. There was no association between breastfeeding and depressive symptoms Hailemariam et al [ 32 ] Exploring COVID-19 Related Factors Influencing Antenatal Care Services Uptake: A Qualitative Study among Women in a Rural Community in Southwest Ethiopia Journal of primary care & community health Qualitative study (in-depth interviews and focus group) Ethiopia Antenatal care There was a decline in antenatal care service uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Some women could not leave their homes due to the imposed lockdowns or lack of transportation to health care facilities [ 30 ]. One study reported a positive correlation between not attending health clinics and breast feeding [ 31 ]. Pandemic-related anxiety was also highlighted as a reason for delayed care or reduced service utilization by pregnant women and children [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Beliefs around insufficient production of breastmilk were linked to limited food availability and inadequacies in maternal dietary intake. In a survey of South Africa women, those ‘who went to bed hungry’ were less likely to breastfeed (Sayed et al, 2021 ). This study is one of the first exploring the profound impact of the COVID‐19 pandemic on dietary quality, meal frequency, and quantity of food consumed by pregnant and lactating women in sub‐Saharan Africa.…”
Section: Discussionmentioning
confidence: 99%